Determining the parameters of arable land fragmentation - Piotr Bożek (Geodesy and Cartography, 2019)
Unfavorable spatial structure of arable land located in Małopolska is a majorobstacle in conducting agricultural activity. Arable lands located in the southern part ofMałopolska are fragmented, have small area, and irregular shapes. Agricultural activity onland with an unfavorable spatial structure is associated with an increase in production costs,which directly results in lower income of farms. One of the methods of improving spatialconditions is to implement land consolidation works. They allow to organize the spatialstructure, increase the area of agriculturally used parcels, while reducing their number. Thearticle presents a new approach in determining the parameters of land fragmentation. GIStools were used to identify areas with unfavorable spatial parameters. The methodologywhich allows for the processing, filtration of source data, determination and visualizationof land fragmentation parameters is discussed. As part of the research, the Binning methodwas used, which allows to visualize the phenomenon and simultaneously reduce the dataused. In the work, a detailed assessment of land fragmentation parameters was made, whichcan be used in agricultural land management works. Analyzes have shown that the southernareas of the Nowy Targ County are characterized by intensive fragmentation of arable land.There are also unfavorable parameters related to the elongation and shape of parcels in thediscussed areas.